Effectiveness Of Integrated Nutrition Intervention In Reducing Anaemia Among Adolescent Girls In Senior High School - Budi, Ananta Kusuma (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Anemia is still a health problem throughout the world, including Indonesia. Anemia in adolescents has a serious impact and is entirely a consequence of iron deficiency which is closely related to the severity of anemia. In addition, anemia in adolescent girls can increase the risk of developing anemia during pregnancy. This will have a negative impact on growth and the fetus in the womb, along with the development to experience a number of complications during pregnancy and during delivery. Anemia can be treated with various strategies, one of which is through nutrition education. This literature review study aims to provide an overview of various methods, media, roles and effectiveness of nutrition education in the context of preventing anemia in adolescents in Indonesia. The method used in this paper is a literature review study by searching Indonesian language articles through the Google Scholar database and Garuda Portal in the period 2018-2021. The keywords used are